2012
DOI: 10.1128/jcm.01718-12
|View full text |Cite
|
Sign up to set email alerts
|

Targeting both rs12979860 and rs8099917 Polymorphisms with a Single-Tube High-Resolution Melting Assay for IL28B Genotyping

Abstract: A rapid, duplex, high-resolution melting interleukin-28B gene (IL28B) genotyping assay, targeting both rs12979860 and rs8099917 polymorphisms, was developed and validated using 30 DNA samples from healthy volunteers. A linkage study on 300 healthy Singaporeans showed variable haplotypes. When the assay was applied to plasma DNA from 50 hepatitis C virus genotype-1 (HCV-1)-infected patients, five compound heterozygous types were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Poon et al have recently reported, this method can be readily adopted by any molecular diagnostic laboratory with HRM capability and will be clinically beneficial in predicting treatment response in HCV genotype 1 infected patients, also this method was sensitive and cost-effective (Poon et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Poon et al have recently reported, this method can be readily adopted by any molecular diagnostic laboratory with HRM capability and will be clinically beneficial in predicting treatment response in HCV genotype 1 infected patients, also this method was sensitive and cost-effective (Poon et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Blood collection on filter paper requires a small amount of sample, is minimally invasive and produces a specimen that is inexpensive to ship and needs no special storage conditions. The extremely high sensitivity of this technology, which is able to study a very low amount of DNA recovered from DBS samples, could potentially allow similar studies in Brought to you by | Universitat de Barcelona Authenticated Download Date | 4/27/18 7:13 PM residual DNA which remains in standard clinical serum samples [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, there is a significantly higher SVR of 73.8% among patients with hepatitis C genotype 1 infection that is similar to Korea [ 9 ] and Taiwan [ 10 ]. This may be due to the IL28B CC polymorphism prevalent in our predominantly Chinese population [ 17 ]. Singapore comprises 74.3% Chinese, 13.3% Malays and 9.1% Indians [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IL28B CC genotype, which is the favourable genotype, is the predominant genotype in China [ 16 ]. Singapore, which is a multi-ethnic country with a predominantly Chinese population, also demonstrates a high proportion of CC genotype [ 17 ].…”
Section: Introductionmentioning
confidence: 99%